A potent antibacterial indole alkaloid from Psychotria pilifera. Issue 8 (2nd August 2016) - Liu, Lu; Song, Chang-Wei; Khan, Afsar; Li, Xiao-Ning; Yang, Xing-Wei; Cheng, Gui-Guang; Liu, Ya-Ping; Luo, Xiao-Dong
Abstract: A new strychnine alkaloid, 16, 17, 19, 20–tetrahydro–2, 16–dehydro–18–deoxyisostrychnine (1 ), and fourteen known alkaloids were isolated from the leaves of Psychotria pilifera . Their structures were identified on the basis of extensive spectroscopic analysis, as well as by comparison with the reported spectroscopic data. The new alkaloid (1 ) exhibited potent antibacterial activity against Escherichia coli, equivalent to cefotaxime with MIC value of 0.781 μg/ml.